Evaluation Of Mulching Mats Derived From Rice Straw And Oil Palm Empty Fruit Bunches For Weed Control - Alloub, Hala Eltahir (1999)
Field experiments were conducted at Universiti Putra Malaysia during 1998 under annual and permanent orchard cropping systems to evaluate oil palm empty fruit bunch (OPEFB) and rice straw (RS) mats, with and without metolachlor as preemergence herbicide, for weed control efficacy, metolachlor activity and soil nutrient status. Under the annual cropping system, three RS mat types (1.5, 1.0, and 0.5 cm thick) and one OPEFB mat type (1.5 cm thick), with and without incorporated metolachlor (1.8 kg/ha) were compared for annual weed control. In the permanent orchard system, two RS mat types (1.5 and 1.0, cm thick) and one OPEFB mat type (1.5 cm thick) with and without incorporated metolachlor (1.8 and 3.6 kg/ha) were compared for perennial weed control. OPEFB mats effectively suppressed annual weed growth. Incorporation of 1.8 kglha metolachlor increased weed control efficacy. Increasing metolachlor to 3.6 kg/ha increased the efficacy of the mats for perennial weed control. However, incorporation of metolachlor 1.8 kg/ha into OPEFB mats had no beneficial effect in controlling perennial grass weed growth compared to mats without herbicide. RS mats without herbicide did not effectively suppress growth of most weeds. Incorporation of 1.8 kg/ha metolachlor enhanced suppression of annual weed growth up to 12 weeks after treatment. At 3.6 kglha metolachlor effectively suppressed perennial weed growth up to 16 weeks after treatment. Root length reduction in rice seedling bioassay was used to evaluate residual phytotoxic activity of field exposed metolachlor treated OPEFB and RS mats. At both metolachlor rates no inhibitory activity was evident in mats sampled after 8 weeks of exposure in the field. OPEFB mats markedly increased soil organic matter (10.6%), organic carbon (10.6%), phosphorous (15.3%) and potassium (49.<)010) with negligible increase in nitrogen (5.6%). Contribution by triple layered RS mats to soil organic matter (9.3%), organic carbon (9.3%) potassium (73.8%) and phosphorous (18.7%) was greater than contributions from single or double layered RS mats. The results of this study showed that OPEFB mats incorporated with 3.6 kg/ha metolachlor have excellent potential for weed control around newly transplanted trees and shrubs. Triple layered RS mats in combination with 3.6 kg/ha metolachlor can also be used to effectively control weeds under young perennial crops.